Про оборотність оператора d/dt + A в деяких функціональних просторах - Городній, М.Ф. (Український математичний журнал, 2007)
Доказано, что оператор d/dt+A, построенный с помощью секториального оператора A со спектром в правой полуплоскости C. является непрерывно обратимым в пространствах Соболева W¹p(R,Dα),α ≥ 0. Здесь Dα — область определения оператора A^α, норма в Dα — норма графика оператора A^α. We prove that the operator d/dt+A constructed on the basis of a sectorial operator A with spectrum in the right half-plane of C is continuously invertible in the Sobolev spaces W¹p(R,Dα),α ≥ 0. Here, Dα is the domain of definition of the operator A^α and the norm in Dα is the norm of the graph of A^α.